The Value of Religious Education in The Novel Cahaya Bening From Jambi By Dr. Oky Pratama - Rahmah, Ulfa Khoiratul; Haris Supratno (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research aims to find and describe the problem of the value of religious education as reflected in the novel Cahaya Bening dari Jambi by Dr. OK, Pratama. It is hoped that the results of this research can contribute to the development of literature in general and the sociology of literature in particular. This research method uses qualitative methods and the data source for this research is the novel Cahaya Bening from Jambi. Data collection techniques use library study techniques or documents in the form of novels. Meanwhile, data analysis techniques use descriptive analysis techniques and content analysis. The results of this research are the novel Cahaya Bening from Jambi by Dr. Oky Pratama, this novel contains a lot of religious values ​​related to humans as religious creatures.